2008
DOI: 10.4314/ajhs.v13i1.30816
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors affecting malaria parasite prevalence in rural Bolifamba, South- West Cameroon

Abstract: SUMMARYThe impact of some environmental factors on malaria parasite prevalence was investigated in rural Bolifamba, Cameroon. The study population comprised 1454 subjects aged 0 -65 years. Malaria parasite prevalence was higher in the rainy (50.1%) than in the dry season (44.2%) with a significant difference (P=0.001) in mean parasite density between seasons. Individuals <15 years old, had significantly higher malaria parasite prevalence (55.5%) than those >15 years (37.4%). Malaria parasite prevalence (P=0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
55
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 10 publications
10
55
5
Order By: Relevance
“…In contrast, participants without electricity in the home were moderately more likely to have KS (OR=1.9; 95% CI 0.9, 4.5; p=.1028) as did participants who did not sleep under a mosquito net (OR=1.9; 95% CI 1.2, 2.9; p=.006). Although electricity in the home and use of a mosquito net can indicate higher income and education [31,32] higher SES was not associated with KS risk in our study, so use of a mosquito bed net represents some other protective effect. Plasmodium parasitemia has previously been shown to be a risk factor for KSHV infection [28], and a possible association between malaria and development of KS merits further investigation.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In contrast, participants without electricity in the home were moderately more likely to have KS (OR=1.9; 95% CI 0.9, 4.5; p=.1028) as did participants who did not sleep under a mosquito net (OR=1.9; 95% CI 1.2, 2.9; p=.006). Although electricity in the home and use of a mosquito net can indicate higher income and education [31,32] higher SES was not associated with KS risk in our study, so use of a mosquito bed net represents some other protective effect. Plasmodium parasitemia has previously been shown to be a risk factor for KSHV infection [28], and a possible association between malaria and development of KS merits further investigation.…”
Section: Discussioncontrasting
confidence: 53%
“…Although malaria is endemic throughout Cameroon, the coastal South and Southwest regions have the highest prevalence of malaria in the country [31,35]. Conversely, individuals in higher altitude regions in the North may be more susceptible to KS due to increased exposure to volcanic and iron-rich soils [18,36].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these children lived in plank houses, which most often have breaks, and crevices on the walls and these allow for easy passage of mosquitoes and consequently higher malaria prevalence. NkuoAkenji et al (23) showed that the prevalence of malaria was significantly higher in children living in plank houses than in those living in cement brick houses. In general, poorer populations which are more often found in rural areas are at greater risk of vector contact and infection, owing to physical proximity to water sources and lowered capacity (lack of education and resources) to use health care services and preventive measures to protect against malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria transmission is perennial in all regions of Cameroon including the BHD where almost all citizens fall ill with it each year [2]. The National Malaria Control Program (NMCP) report of activities shows that in the South West Region of Cameroon, 56% of consultations, 54% of hospital admissions and 53% of deaths among children below five years are due to malaria [3].…”
Section: Introductionmentioning
confidence: 99%